1978
DOI: 10.1002/path.1711240109
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of the lung in the rat following exposure to crocidolite asbestos and quartz

Abstract: Lung tissue from rats that had inhaled U.I.C.C. crocidolite asbestos or quartz particles showed thickening of the interstitial tissue and the presence of collagen fibres. Aggregates of macrophages in the alveolar spaces were a dominant feature of all the sections examined from asbestos exposed rats. According to the ultrastructural studies described here, all the macrophages were mature cells, indicating that the ingested crocidolite asbestos was non-toxic. Lung sections of rats exposed to quartz particles wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Type II cell hyperplasia following asbestos inhalation has been reported previously (Davis, 1963;Miller et al, 1978); however, these studies did not involve the short exposure periods used in this experiment and only gave subjective opinions of the changes in type II cell numbers. This is the first report of a rapid increase in cell numbers following dust exposure and thus suggests an initial direct action of the dust on type II cells rather than a response mediated by factors produced by other cell types.…”
Section: Discussionmentioning
confidence: 85%
“…Type II cell hyperplasia following asbestos inhalation has been reported previously (Davis, 1963;Miller et al, 1978); however, these studies did not involve the short exposure periods used in this experiment and only gave subjective opinions of the changes in type II cell numbers. This is the first report of a rapid increase in cell numbers following dust exposure and thus suggests an initial direct action of the dust on type II cells rather than a response mediated by factors produced by other cell types.…”
Section: Discussionmentioning
confidence: 85%
“…After ingestion of asbestos, macrophages developed large flattened pseudopodia, an increase in cytoplasmic blebbing, asbestos bodies and more extensive cytoplasmic processes (60,93). The cytoplasm was filled with numerous lysosomes, free and aggregated ribosomes, mitochondria, and strands of rough endoplasmic reticulum (94). After ingestion of quartz, macrophages showed pronounced intracytoplasmic vacuolation deterioration of the plasma membrane and assumed wild, bizarre shapes (95).…”
Section: Morphological Alterationsmentioning
confidence: 99%
“…This hypothesis is based on the results of previous investiga tions showing different morphological and functional re sponses of alveolar, pleural, and peritoneal macrophages to different mineral particles. Miller and Kagan [10,II] and Miller et al [12] observed different ultrastructural characteristics of rat alveolar and peritoneal macrophages following exposure to silica particles or crocidolite asbes tos fibers. Macrophages isolated from animals exposed to silica were vacuolated, did not spread in culture, and showed morphologic evidence of membrane damage [II], In contrast, macrophages isolated from animals after exposure to crocidolite asbestos showed morphologic evi dence of activation [ 10,12], Other investigators observed that a single intraperitoneal injection of 2.5 mg of croci dolite or chrysotile asbestos fibers in mice increased mac rophage spreading and decreased phagocytosis, but did not increase their ability to kill tumor cells [ 13].…”
Section: Introductionmentioning
confidence: 99%